2021
DOI: 10.1039/d1qo00592h
|View full text |Cite
|
Sign up to set email alerts
|

Controllable chemoselectivity in the reaction of 2H-indazoles with alcohols under visible-light irradiation: synthesis of C3-alkoxylated 2H-indazoles and ortho-alkoxycarbonylated azobenzenes

Abstract: A high chemoselectivity of visible-light-induced reaction of 2H-indazoles with alcohols controlled by the reaction atmosphere (N2 or O2) was developed. Under N2 atmosphere, an alkoxylation of 2H-indazoles with alcohols in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…In 2021, Wang and co-workers reported a highly chemoselective visible-light-induced reaction of 2 H -indazoles with alcohols under the atmosphere of N 2 and O 2 (Scheme 37). 60 Under an N 2 atmosphere, the C3-alkoxylation of 2 H -indazoles with alcohols using Mes-Acr + ClO 4 − as a photosensitizer and Selectfluor as an oxidant afforded C3-alkoxylated 2 H -indazoles in good to excellent yields. Notably, ortho -alkoxycarbonylated azobenzenes were delivered in good yields when conducted under an O 2 atmosphere and in the absence of Selectfluor via the ring opening of 2 H -indazoles.…”
Section: Direct C3–h Functionalization Of 2h-indazolesmentioning
confidence: 99%
“…In 2021, Wang and co-workers reported a highly chemoselective visible-light-induced reaction of 2 H -indazoles with alcohols under the atmosphere of N 2 and O 2 (Scheme 37). 60 Under an N 2 atmosphere, the C3-alkoxylation of 2 H -indazoles with alcohols using Mes-Acr + ClO 4 − as a photosensitizer and Selectfluor as an oxidant afforded C3-alkoxylated 2 H -indazoles in good to excellent yields. Notably, ortho -alkoxycarbonylated azobenzenes were delivered in good yields when conducted under an O 2 atmosphere and in the absence of Selectfluor via the ring opening of 2 H -indazoles.…”
Section: Direct C3–h Functionalization Of 2h-indazolesmentioning
confidence: 99%
“…Recently (June 2021), the Wang and Li group 37 reported a highly chemo-selective visible light induced reaction of 2 H -indazoles with alcohol in the presence of Mes-Acr + ClO 4 − as a photocatalyst and Selectfluor as an oxidant under 1.5 W blue LED irradiation and under a N 2 atmosphere (Scheme 19). Under the optimized conditions, C-3 alkoxylation of 2 H -indazole ( 28a ) with various alcohol derivatives ( 35 ) was explored.…”
Section: C-functionalizationmentioning
confidence: 99%
“…In 2021, Li's group [34] explored a transition metal-free, visible light-mediated C(sp 2 )-O coupling reaction between 2H-indazoles and alcohols in the presence of Acr + -MesClO 4 as the photocatalyst and Selectfluor as the oxidant (Scheme 5). It was found that the reaction efficiency of the linear primary alcohol was satisfactory.…”
Section: Methylene Blue Catalytic Systemmentioning
confidence: 99%